Pemodelan Tarikan Pergerakan Pengunjung pada Pasar Cakke Kecamatan Anggeraja Kabupaten Enrekang - Nur Afiat; Hamka Hamka; Hendro Widarto; Adnan Adnan (Student Research Journal, 2024)
This research is motivated by the trade of various kinds of products so that the growth and development of many trading areas have sprung up both managed by the government and the private sector. The existence of this market can provide a large enough visitor attraction so that it can affect land use which results in irregular crowds that affect the performance of road sections resulting in congestion on the road. The purpose of this study is to determine the factors that influence the attraction of cakke market visitor movements and the model of attraction of cakke market visitor movements. By distributing questionnaires and interviews to market visitors. The study used the SPSS version 24 application to analyse the data using the correlation and multiple linear regression test methods. The results showed that the factors affecting the amount of attraction of visitor movements based on the results of correlation analysis which showed that there was a strong correlation between hygiene conditions to the attraction of 0.604; and building conditions to the attraction of 0.657; while the correlation that showed a medium between the distance of the house to the attraction of 0.537: total shopping to the attraction of 0.535; and the quality of goods to the attraction of 0.542; while the correlation that showed a low value between parking conditions to the attraction of 0.350 and multiple linear equation models showed the following equation: Y = 0.192 + 0.135x1 + 0.161x2 + 0.206x3 + 0.300x4 + 0.070x5 + 0.124x6.